Madagascar : Debt Management Performance Assessment - World Bank (Washington, DC, 2015)
Madagascar's central government debt stood at around 30 percent of gross domestic product (GDP) in 2011. Due to political developments in 2008-2009, the Acting government of Madagascar has limited borrowing opportunities from both external and domestic lenders. This situation is expected to change after the upcoming general elections planned for mid-2013. The legal framework for government debt management is unclear in some parts and in general underdeveloped. Thus, for 2013 fiscal year, the Parliament has authorized the government to borrow internally and externally for the implementation of various development projects. There are no specific debt management objectives, no requirement to develop a debt management strategy, and no evaluation process reflected in the primary legislation. An important step has been taken by reorganizing the Public Debt Directorate (PDD) of the Ministry of Finance and Budget as the Principal DeM entity of the government. It manages both external and domestic debt, and takes part in all loan negotiations. Yet to be prepared is a debt statistical bulletin and a comprehensive DeM strategy. There was one external compliance audit prepared in 2011 for the period of 2006-2008, but no performance audits. The final audit report was developed in 2012, but is not made public. There is no formal or informal debt management strategy in Madagascar. There is also no evaluation and disclosure of information on public government debt management. The debt statistical bulletin, prepared during 2012, is still in a draft form.